(3GdVQGFH GdeMdjI aj GdJTQjY GdeUQj hGdebGQf (B/s - (3CfhQ YHO GdSdGe GdbHGfjs; (3YHO GdMcje GdQaGYjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQIs, 1943)
(3hbO bSe GdHGMK GdQSGdI Edi KdGKI CHhGH(B- (3GdHGH GdChd(B: (3Jcde ajg Yf HYV GdeHGOF GdYGeI hYf GdeSGFd GdfXQjI GdJj JKjQgG acQI GdVQjHI GdeMdjI, GdHGH GdKGfj(B: (3HMK ajg JWhQ GdVQGFH GdeMdjI aj eNJda GdOhd eaQOG dcd ef aQfSG hCdeGfjG hEfLdJQG aUdG NGUG(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdeGdjI GdYGeI hGdJTQjY GdVQjHj (B1943.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: (3UaMI (B348-352.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdVQGFHs; (3aQfSGs -- (3bhGfjf hJTQjYGJs; (3CdeGfjGs -- (3bhGfjf hJTQjYGJs; (3GdeedcI GdeJMOIs -- (3bhGfjf hJTQjYGJs; (3GdeGdjI GdeMdjIs; (3GdNOeGJ GdYGeI GdbhejI s; (3GdNOeGJ GdYGeI GdeMdjIs; (3GdVQjHI GdeMdjI s; (3GdVQjHI GdYGeIs; (3GdVQjHI GdTNUjIs; (3GdVQjHI GdYjfjI s; (3GdVQGFH GdEbdjejIs; (3GdVQGFH GdYbGQjIs; (3GdeGd GdeTJQcs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjY GdVQjHjs